Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1111/exd.12231
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sphingoid bases on the sphingolipidome in early keratinocyte differentiation

Abstract: Keratinocyte sphingolipids are structural elements of epidermal permeability barrier and potential regulators of epidermal functions. We tested the influence of sphingoid bases sphinganine, sphingosine and phytosphingosine on in vitro keratinocyte differentiation. Lipidomic and transcriptomic analysis after treatment emphasizes sphinganine and phytosphingosine as potent modulators of keratinocyte differentiation and lipid metabolism. Sphinganine treatment regulated differentiation and sphingolipid metabolism-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 30 publications
1
20
2
Order By: Relevance
“…As reported by other groups, we confirmed that ceramide NP species markedly increased in cultured KC upon the treatment of PHS by the HPTLC analysis, which is consistent with the previous reports (Sigruener et al, ). In Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As reported by other groups, we confirmed that ceramide NP species markedly increased in cultured KC upon the treatment of PHS by the HPTLC analysis, which is consistent with the previous reports (Sigruener et al, ). In Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Our previous study showed that PHS enhanced both biosynthesis and degradation pathways of filaggrin, which eventually resulted in increasing the natural moisturizing factor (NMF) in human skin (Choi et al, ). Recently, Sigruener et al reported that all three sphingoids, SPH, DHS, and PHS, showed strong regulatory effects on genes involved in KC differentiation and CER biosynthesis (Sigruener et al, ). Particularly, they claimed that DHS stimulated general biosynthetic processes of all different CER in SC.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that Sph produced by the action of CerN is converted to S1P and induces production of inflammatory mediators in human keratinocytes46. In addition, exogenous Sph, dihydroSph, and phytoSph are found to be modulators of differentiation and lipid metabolism in keratinocytes4748. These observations indicate that CerN disturbs the skin barrier function by decreasing the levels of skin Cer and by increasing the long-chain bases.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Paragh et al [ 80 ] demonstrated that DHS also promotes the differentiation of keratinocytes. Finally, Sigruener et al [ 81 ] demonstrated that treatment with PHS and DHS increase the levels of phytoceramides and very long-chain ceramides, respectively and leads to the differentiation of keratinocytes. Collectively, this suggests that either sphingoid bases, phytoceramides, and/or ceramides mediate keratinocyte differentiation.…”
Section: Intracellular Ceramides and Their Metabolites Regulate Epidementioning
confidence: 99%